Macrophage migration inhibitory factor (MIF) acetylation protects neurons from ischemic injury - Jin-Xia Hu; Wei-Jing Ma; Li-Ying He; Cong-Hui Zhang; Cheng Zhang; Yan Wang; Chao-Nan Chen; Da-Yong Shen; Hui-Min Gao; Rui-Ru Guo; Qian-Qian Ning; Xin-Chun Ye; et al. (Cell Death and Disease, 2022)
Abstract Ischemia-induced neuronal death leads to serious lifelong neurological deficits in ischemic stroke patients. Histone deacetylase 6 (HDAC6) is a promising target for neuroprotection in many neurological disorders, including ischemic stroke. However, the mechanism by which HDAC6 inhibition protects neurons after ischemic stroke remains unclear. Here, we discovered that genetic ablation or pharmacological inhibition of HDAC6 reduced brain injury after ischemic stroke by increasing macrophage migration inhibitory factor (MIF) acetylation. Mass spectrum analysis and biochemical results revealed that HDAC6 inhibitor or aspirin treatment promoted MIF acetylation on the K78 residue. MIF K78 acetylation suppressed the interaction between MIF and AIF, which impaired MIF translocation to the nucleus in ischemic cortical neurons. Moreover, neuronal DNA fragmentation and neuronal death were impaired in the cortex after ischemia in MIF K78Q mutant mice. Our results indicate that the neuroprotective effect of HDAC6 inhibition and aspirin treatment results from MIF K78 acetylation; thus, MIF K78 acetylation may be a therapeutic target for ischemic stroke and other neurological diseases.